Skeletons in the closet : transitional justice in post-Communist Europe - Nalepa, Monika, 1976- (Cambridge studies in comparative politics., 2010)
"This book tackles three puzzles of pacted transitions to democracy. First, why do autocrats ever step down from power peacefully if they know that they may be held accountable for their involvement in the ancien regime? Second, when does the opposition indeed refrain from meting out punishment to the former autocrats once the transition is complete? Third, why, in some countries, does transitional justice get adopted when successors of former communists hold parliamentary majorities?" "Monika Nalepa argues that infiltration of the opposition with collaborators of the authoritarian regime can serve as insurance against transitional justice, making their commitments to amnesty credible. This explanation also accounts for the timing of transitional justice across East Central Europe. Nalepa supports her theory using a combination of elite interviews, archival evidence, and statistical analysis of survey experiments in Poland, Hungary, and the Czech Republic."--Jacket.